2015
DOI: 10.2989/16085906.2015.1016981
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of women and men living with HIV and their healthcare providers towards pregnancy and abortion by HIV-positive women in Nigeria and Zambia

Abstract: Fertility decisions among people living with HIV/AIDS (PLWHA) are complicated by disease progression, the health of their existing children and possible antiretroviral therapy (ART) use, among other factors. Using a sample of HIV-positive women (n = 353) and men (n = 299) from Nigeria and Zambia and their healthcare providers (n = 179), we examined attitudes towards childbearing and abortion by HIV-positive women. To measure childbearing and abortion attitudes, we used individual indicators and a composite mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Given the high rates of abortion stigma in Zambia (Geary et al 2012;Moore et al 2015;Cresswell et al 2016;Footman et al 2021), it is unsurprising that opponents emerged as the modal latent class in the present study. This is consistent with findings from a household survey conducted two years prior in the study area, which found that 15 percent of Zambian women supported legal abortion regardless of the circumstances motivating abortion careseeking (Cresswell et al 2016).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Given the high rates of abortion stigma in Zambia (Geary et al 2012;Moore et al 2015;Cresswell et al 2016;Footman et al 2021), it is unsurprising that opponents emerged as the modal latent class in the present study. This is consistent with findings from a household survey conducted two years prior in the study area, which found that 15 percent of Zambian women supported legal abortion regardless of the circumstances motivating abortion careseeking (Cresswell et al 2016).…”
Section: Discussionmentioning
confidence: 78%
“…A theoretically informed set of demographic, social, and behavioral factors-including age (Bantie et al 2020;Cresswell et al 2016); educational attainment (Kavanaugh et al 2013;Mosley et al 2017); household wealth (Thomas, Norris, and Gallo 2017); place of residence (Holcombe, Berhe, and Cherie 2015;Scoglio and Nayak 2023;Smith et al 2022); religiosity (Biggs et al 2023;Gutema and Dina 2022;Silva et al 2009); and pregnancy/fertility experiences (Moore et al 2015;Woodruff et al 2018)-were identified a priori from the extant literature and assessed independently of other covariates in mixture modeling. Measured predictors of latent class membership included parity (nulliparous vs. multiparous); future fertility intentions (desires no [more] child [ren] or undecided vs. desires a[nother] child [ren]); current contraceptive use (any modern contraceptive use vs. no contraceptive use or traditional methods only); number of family planning (FP) message sources (i.e., radio, television, newspaper/print media, community events) recalled in the past three months (range: 0-4); religiosity, measured continuously using a three-item, 5-point (definitely not true to definitely true) scale assessing the depth and magnitude of participation in religious activities (Cronbach's alpha: 0.88) (Gallagher 2018); and perceived immorality of abortion (endorsement of the statement, "Abortion is immoral"), measured ordinally on a 5-point scale (strongly disagree to strongly agree).…”
Section: Discussionmentioning
confidence: 99%
“…However, they faced conflicts between guaranteeing these rights and preventing HIV dissemination, 19 and attention was more focused on women. 20 For cultural and/or structural reasons, men were, for many years, virtually excluded from health care services and involvement with reproductive matters. 21 Only more recently have we seen the creation of public health care policies directed at this population.…”
Section: Discussionmentioning
confidence: 99%
“…The design and implementation of the two surveys, one community-based and one facility-based, have been described in-depth elsewhere (Bankole et al, 2013; Moore, Bankole, Awolude, Audam, & Oladokun, 2014). In both surveys, the women were age 15–49 and the men were age 15–59.…”
Section: Methodsmentioning
confidence: 99%